النبر والتنغيم في اللغة العربية واللغة الصينية الماندرين : دراسة تحليلية تقابلية - سيو، شاو بينغ (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Language sounds are an important characteristic of the human language, and the vocal expression of the language is for human communication with others; therefore, the voices of language have an important role in all languages of the world.The study searches in the characteristics of stress and intonation in Arabic and Chinese Mandarin, and compares between them by highlighting the similarities and differences between both languages, the research aims to know the stress and intonation in Arabic language and a statement of similarities and differences between them. The research will follow the descriptive approach and the analytical approach. The result of this study are as follow: The first part of the Arabic language begins only by consonant; the Chinese language begins the syllable with consonant and ends with a vowel, and there is a difference in the composition of the sounds between the two languages, such as letters (M, N, P, L) It pronounced as the same sounds in Mandarin; there are also common sounds between the two languages such as ( يِ) (وْ) (آ ), and they pronounced as the same sounds in Mandarin; the word for Mandarin is different from Arabic; Only one voice; Mandarin is a lingua franca, and the five are the basic components of Chinese words To date; however, the intonation in Arabic language are not a part of speech and cannot used to distinguish the meaning of intonation, we can change the stress in places between the vocal sections; that only expresses the position of the speaker and feelings.